Analisis Kemampuan Berpikir Kreatif Mahasiswa PGSD Dalam Mendesain Soal Tes Bentuk Uraian Untuk Meningkatkan Soft Skills Mahasiswa - Susanti Faipri Selegi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
The purpose of this research was to know creative thinking skills of PGSD’s students to design the essay test to increase student’s soft skills. Subject of research are students in 4 semester that consist of 45 students. Method of this research is qualitative research with date collecting technique by test and documentation. The result of research show that 53,3% of 45 students achieved the good score. The students could be able elaborated the essay test through the creativity using by picture in order to student in elementary school understand it. The essay test which had been made more creative and adjusted cognitive level. Furthermore, 8,88% of 45 students achieved the enough categories and 2,22% achieved the less category. This is due to the essay test not being able to develop the material properly, both from grids and scoring guidelines. Overall the average value obtained is 77,42% in the good category. Thus, students’ creative thinking skills such as fluency, flexibility, originality, and elaboration can improve students’ soft skills in designing the essay test in 5th grade elementary school.